Relationship of Chlorophyll a Concentration to Seasonal Water Quality in Lake Manatee, Florida - Craig D. Stanley; R. A. Clarke; Brian L. McNeal; B. W. Macleod (EDIS)
The primary objectives of this study were to determine if a significant relationship existed between levels of selected water quality parameters and Chl a concentration in Lake Manatee, and to develop a predictive equation for estimating when water quality conditions were conducive to high Chl a levels. This is document SL-211, a publication of the Soil and Water Science Department, Florida Cooperative Extension Service, IFAS, University of Florida. Published November 2003.